"--are you gonna wait until it kills you or are you gonna kill it?'' : narratives of individuals dependent on crystal methamphetamine - Ajodah, Anju (2008)
Includes bibliographical references (leaves 125-136).The aim of this study was to investigate the current crystal methamphetamine problem and its trends of abuse as manifested in the local context of Cape Town, South Africa. Twelve individuals (four ex-users, five users in recovery and three current users) who were dependent on crystal methamphetamine took part in the study. They ranged between the age of seventeen and twenty eight years. Semi-structured interviews were conducted in order to gather participants' stories about their subjective understanding of their dependence on crystal methamphetamine. Onset of use was often driven by curiosity and/or peer pressure, as well as to avoid states of psychological discomfort. Crystal methamphetamine use was usually maintained due to the enjoyment of its rewarding effects. Smoking the substance became especially important with more regular use as it served as a powerful, albeit temporary, stress eliminator. Crystal methamphetamine ubiquity appeared to be highly influential in the onset as well as maintenance of the substance's consumption. A range of debilitating physiological and psychological symptoms comprised the state of dependence. The presence of psychotic symptoms was rife within the sample and was often indicative of severe and prolonged crystal methamphetamine use. An inability to function within the external 'drug-free reality' was characterised by participants not being able to fulfill responsibilities and thus was also suggestive of maladaptive patterns of use. Polydrug use was generally common among participants. Some female participants' narratives also pointed towards the association of crystal methamphetamine use and sexual risk-taking behaviours. Identifying an external motivating factor was important in encouraging cessation of use but internal motivation often appeared to be just as significant in attaining as well as sustaining abstinence. Sleeping was the most common strategy used in dealing with the state of severe withdrawal which followed post use. In general, most participants did not perceive treatment as being the most useful means of achieving sobriety. Identifying goals and a perceived sense of purpose appeared important in motivating the individual along the path towards recovery as well as in the maintenance of abstinence